Strategies for Halal Product Validation and MSME Collaboration to Enhance the Competitiveness of Local Snacks in the Digital Era: Strategi Validasi Kehalalan Produk dan Kolaborasi UMKM dalam Meningkatkan Daya Saing Camilan Lokal di Era Digital - Arbansyah; Rahim, Abdul; Barito, Raditya Andromeda; Nurdin, Andi; Ilham, Muhammad Fauzan Nur; Latipah, Johar (Journal of Empowerment and Community Service (JECSR), 2025)
The rapid development of digital technology has transformed the marketing landscape for micro, small, and medium enterprises (MSMEs), particularly in the local snack industry. However, ensuring product competitiveness requires not only innovative marketing strategies but also the validation of product halalness, which is crucial for consumer trust in Indonesia. This community engagement program aimed to assist MSMEs in Samarinda in validating the halal status of their flagship products, Basreng (fried meatballs) and Sus Kering (dry choux pastry), while simultaneously strengthening collaboration for digital marketing. The method involved participatory workshops, direct mentoring, and collaborative content creation using platforms such as Instagram and Shopee. The findings indicate that halal validation was achieved through careful selection of raw materials, adherence to cleanliness standards, and transparent production processes. In addition, the collaborative approach with MSMEs fostered the creation of attractive branding and effective digital content, significantly increasing product visibility and consumer confidence. The proposed solution emphasizes the integration of halal assurance and digital marketing, which can serve as a model for other local snack MSMEs to enhance their competitiveness in the digital era.